Foreword - Ledo, Jorge (Analysis. Journal of Philosophical Research, 2018)
The aim of this volume is not to offer a comprehensive overview of the multifarious aspects of fiction and its implications for early modern philosophy, but to be an invitation, from the standpoint of the history of philosophy, to survey some of the fundamental problems of the field, using six case-studies written by some of the finest international scholars in their respective areas of Renaissance studies. Although perhaps not evident at a first reading, these six studies are linked by common concerns such as the theoretical relationship between (literary) history, rhetoric, poetics, and philosophy; the tensions between res, verba, and imago; and the concept of enargeia. They have been arranged according to the chronology of the corpus each one considers.